Putative protein kinase product of the Drosophila segment-polarity gene zeste-white3. - Siegfried, E.; Perkins, L.A.; Capaci, T.M.; Perrimon, N. (Nature, 1990)
The metameric pattern of the Drosophila embryo is regulated by a combination of maternal and zygotic genes. The segment-polarity class of genes are required for the correct patterning within each segmental unit. Mutations in any one of these genes results in deletions and duplications of parts of each segment. The segment-polarity genes act coordinately by means of local cellular interactions to assign and maintain an identity for each cell in the segment, and to establish segment boundaries. Here we describe the molecular characterization of a novel segment-polarity gene, zeste-white3 (zw3). Embryos derived from germ lines that are homozygous for zw3 mutations (zw3 embryos) have phenotypes similar to embryos that are mutant for the segment-polarity gene naked (nkd). These embryos lack most of the ventral denticles, which are differentiated structures derived from the most anterior region of each segment. We have isolated the zw3 gene and compared the structure of one maternal and one zygotic transcript encoded by the gene. The zw3 gene is unique among the segment-polarity genes so far characterized, in that it encodes proteins that have homology to serine-threonine protein kinases. This indicates that zw3 may play a part in a signal transduction pathway involved in the establishment of cell identity within each embryonic segment.